Determination of high school students' views and knowledge on substance abuse - Altunkürek, Şerife Zehra; Özer, Esra Nur (Journal of Dependence, 2020)
Objective: This study aimed to determine opinions and knowledge of high school students about substance use and abuse.Method: This study is carried out between January and March 2020 with 515 high school students aged between 14 and 18 and from 3 different high schools in Ankara. A questionnaire searching for views and knowledge on subtance abuse and a sociodemographic form were prepared and applied by researchers.Results: 53.2% of the participants were male and 49.5+ of them were in their first year of high school education. 58.6% of the students did not receive any education about substance abuse, 93% of them told that young people should be informed about the issue. Besides 76.9% stated that young people did not have sufficient knowledge about substance abuse. A statistically significant difference is found between students’ gender and their school classes, and their views about substance abuse.Conclusion: High school students need trainings and education about preventing substance abuse . Providing trainings, conferances, seminars to students, families and school managements related to substance addiction prevention could be beneficial.
Keywords: Substance abuse; high school student; nursing; adolescent